Membangun Kompetensi dan Kredibilitas Da’i - Bukhari, Bukhari (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Existence of competent Da’i and credible is very important in the process of dakwah. In achieving the goal of dakwah, it is necessary to build the competence and credibility of the Da’i. Ideally every Da’i should have the competence and credibility. Credibility of the Da’i is preaching trust and confidence to dakwah object, either before or after being preaching. While the Da’i competence is related to the knowledge, abilities, skills, and attitudes in performing their duties Dai’s preaching. The birth of a Da’i's credibility based on its competence Da’is. Thus, the credibility of the Da’i can be built and acquired through education, knowledge and authority of Da’i themselves. As for the steps to build Da’i’s credibility is the Da’i who has the authority of expertise through education and experience. Then, in dakwah the Da’i can refer preaching materials cite sources who have the authority and competence. So, Da’i do dakwah with rational approach and logical argument. In addition, the Da’i also must has good attitudes.